Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers